2005
DOI: 10.1111/j.1420-9101.2005.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in behavioural thermoregulation: local adaptation vs. plasticity in California grasshoppers

Abstract: We investigated the adaptive significance of behavioural thermoregulation in univoltine populations of the grasshopper Melanoplus sanguinipes along an altitudinal gradient in California using laboratory tests of animals raised under different temperatures. Trials consisted of continuous body temperature measurements with semi‐implanted microprobes in a test arena, and observation and simultaneous recording of behavioural responses. These responses included mobility, basking and orientation of the body axes (as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Generally, animals regulate T b to a set point ideal or optimum temperature (Cabanac, 2006). It has been suggested that preferred T b 's have co-evolved with performance optima, particularly those performances that are temperature sensitive (Samietz et al, 2005;Glanville and Seebacher, 2006). In crocodiles many of their behaviours are in water when T b is usually lower than when they are out of the water (Grigg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, animals regulate T b to a set point ideal or optimum temperature (Cabanac, 2006). It has been suggested that preferred T b 's have co-evolved with performance optima, particularly those performances that are temperature sensitive (Samietz et al, 2005;Glanville and Seebacher, 2006). In crocodiles many of their behaviours are in water when T b is usually lower than when they are out of the water (Grigg et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The behavioural mechanisms of thermoregulation are similar among terrestrial ectotherms (Muth, 1977;Seebacher, 1999;Samietz et al, 2005), although actual body temperature is determined by the thermal sensitivities of the biochemical components, particularly enzyme activities, of the organisms (Somero, 1995). The regulated or preferred body temperature of terrestrial ectotherms is thought to have co-evolved with performance optima in response to the dominant thermal signal in the environment (Huey and Bennett, 1987;Samietz et al, 2005). The current view is that temperature-performance curves are non-reversibly centred around the mean (preferred) body temperature of individuals (Angilletta et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Body temperature set-points are controlled by temperature-sensitive neurons that link the animal core and periphery via the hypothalamus (Hammel, 1965;Boulant, 2006;Wechselberger et al, 2006), and thermoregulation may be influenced by endocrine factors that act on a daily or seasonal basis (Lutterschmidt et al, 2003). The behavioural mechanisms of thermoregulation are similar among terrestrial ectotherms (Muth, 1977;Seebacher, 1999;Samietz et al, 2005), although actual body temperature is determined by the thermal sensitivities of the biochemical components, particularly enzyme activities, of the organisms (Somero, 1995). The regulated or preferred body temperature of terrestrial ectotherms is thought to have co-evolved with performance optima in response to the dominant thermal signal in the environment (Huey and Bennett, 1987;Samietz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As has been found in other studies (Samietz et al, 2005), grasshoppers from higher altitudes actively increased their body temperatures more by sun seeking and basking.…”
Section: Microhabitat Selection In Natural Populationsmentioning
confidence: 58%
“…Gillis and Smeigh, 1987;Willott, 1997) relating them to the operative temperature of non-thermoregulating models (Hertz et al, 1993). Field studies on grasshoppers have demonstrated that the proportion of individuals exhibiting behaviours such as basking, stilting or crouching is related to surface temperatures (Chappell, 1983;Gilman et al, 2008;O'Neill and Rolston, 2007;Samietz et al, 2005), but few studies have attempted to measure the change in body temperature accompanying particular behaviours. Basking has been shown to lead to increases in body temperature under exposure to solar radiation, but the effects of passive warming and active thermoregulation are not always distinguished (Carruthers et al, 1992).…”
Section: Introductionmentioning
confidence: 99%